International capital flows, deregulation and the offset coefficient in Finland 1975-1990 - Timo Hämäläinen; Arto Kovanen (Bank of Finland, 1991)
This study examines, using variable-parameter regression, how the offset coefficient in the capital flow equation for Finland has changed over time. We found the constant parameter estimate of the offset coefficient to be stable and quite large. Instead, the interest rate sensitivity has increased due to the liberalization, i.e. international capital flows have become very sensitive to the interest rate differential. We also examined how international capital flows are affected by exchange rate speculations.
URN:NBN:fi:bof-201908071362
Keywords: 330